Droplet epitaxy quantum dot based infrared photodetectors. (30th March 2020) - Vichi, Stefano; Bietti, Sergio; Khalili, Arastoo; Costanzo, Matteo; Cappelluti, Federica; Esposito, Luca; Somaschini, Claudio; Fedorov, Alexey; Tsukamoto, Shiro; Rauter, Patrick; Sanguinetti, Stefano
Abstract: The fabrication and characterization of an infrared photodetector based on GaAs droplet epitaxy quantum dots embedded in Al0.3 Ga0.7 As barrier is reported. The high control over dot electronic properties and the high achievable number density allowed by droplet epitaxy technique permitted us to realize a device using a single dot layer in the active region. Moreover, thanks to the independent control over dot height and width, we were able to obtain a very sharp absorption peak in the thermal infrared region (3–8 μ m). Low temperature photocurrent spectrum was measured by Fourier spectroscopy, showing a narrow peak at 198 meV (∼6.3 μ m) with a full width at half maximum of 25 meV. The observed absorption is in agreement with theoretical prediction based on effective mass approximation of the dot electronic transition.